DINAMIKA NELAYAN DAN WILAYAH KONSERVASI : ANALISIS SOSIO-KULTURAL DI KAWASAN TAMAN NASIONAL KARIMUNJAWA - Deny Wahyu Apriadi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
The socio-cultural dynamics of fishing communities in the Karimunjawa National Park (TNKJ) area is an interesting analysis for further study. This study focuses on the role of TNKJ in fishing communities. This research use a qualitative method with snowball sampling technique. The data collection in this study used observation techniques and in-depth interviews conducted in Karimunjawa Village, Karimunjawa District, Jepara Regency, Central Java. There are several explanations regarding the socio-cultural conditions of the fishing communities living in the TNKJ area. When the TNKJ area has been inaugurated as a tourist destination, this of course has a direct impact on the community. Problems regarding the zoning system on access to fishing, changes in livelihoods to cultural conflicts that are present in the lives of fishing communities are important things that must be studied more deeply. Strengthening social capital in the life of fishing communities, such as mutual cooperation and sympathy for fellow community members, is the main force that has been maintained until now. This research is able to contribute to socio-cultural studies of the community, especially in life in coastal area